Gel Formulation from Pineapple Leaf Waste with Propylene Glycol Variations for Burn Wound Healing - Vinda Afrilia Adi; Gitanjali Darmawan; Rian Dewi Saputri Azahra; Ferra Delan Jelita (Universitas Muhammadiyah Purwokerto, 2024)
Despite their potential medicinal properties, pineapple leaves (Ananas comosus L. Merr) are an underutilized agricultural waste. These leaves contain flavonoids, which are known for their ability to aid in wound healing, particularly for burns as a gel. Propylene glycol plays an important role in the formulation of gels due to its ability to enhance the penetration and absorption of active compounds, such as flavonoids from the pineapple leaves. It also helps in maintaining the gel's consistency, ensuring it remains stable and effective for topical applications. in this study, varying concentrations of propylene glycol (0%, 10%, 20%, 30%, and 40%) were tested for their efficacy in burn wound healing in Rats. Gel production was prepared by the extraction of pineapple leaf waste and mixed with propylene glycol in varying concentrations (10 -40%) and gel additives. The gel was then applied to burn wound healing in rats. The study involved five groups: four treatment groups receiving gel with propylene glycol concentrations of 10%, 20%, 30%, and 40%, and a control group without using gel. Results indicated that the pineapple leaf gel significantly accelerated burn wound healing compared to the control group. Among the formulations, gels with 20% and 30% propylene glycol concentrations demonstrated the most effective and rapid healing properties. These findings highlight the potential of pineapple leaf extract as an economical and sustainable option for topical burn treatment, encouraging further exploration and optimization of its formulation for clinical applications